2021
DOI: 10.3390/molecules26071867
|View full text |Cite
|
Sign up to set email alerts
|

Methiothepin Increases Chemotherapy Efficacy against Resistant Melanoma Cells

Abstract: We previously reported that methiothepin, a small molecule known as a nonselective serotonin 5-HT receptor antagonist, inhibited the doxorubicin efflux activity of the Hedgehog receptor Ptch1 and enhanced the cytotoxic, pro-apoptotic, anti-proliferative, and anti-clonogenic effects of doxorubicin on adrenocortical carcinoma cells. Here, we show that methiothepin also inhibits doxorubicin efflux and increases doxorubicin cytotoxicity in melanoma cells which endogenously overexpress Ptch1. Melanoma patients havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Methiothepin was also shown to overcome the resistance of BRAF V600E melanoma cells by enhancing the cytotoxicity of the targeted chemotherapies against kinases such as vemurafenib (BRAF inhibitor) and trametinib (MEK inhibitor) leading to melanoma cells death. Importantly, the addition of methiothepin to vemurafenib inhibits the migration of resistant melanoma cells more efficiently than vemurafenib alone [60]. MicroScale Thermophoresis analyses performed on membranes prepared from yeast expressing human Ptch1 confirmed that methiothepin specifically interacts with Ptch1 with a Kd of about 7 mM.…”
Section: Methiothepinmentioning
confidence: 90%
See 1 more Smart Citation
“…Methiothepin was also shown to overcome the resistance of BRAF V600E melanoma cells by enhancing the cytotoxicity of the targeted chemotherapies against kinases such as vemurafenib (BRAF inhibitor) and trametinib (MEK inhibitor) leading to melanoma cells death. Importantly, the addition of methiothepin to vemurafenib inhibits the migration of resistant melanoma cells more efficiently than vemurafenib alone [60]. MicroScale Thermophoresis analyses performed on membranes prepared from yeast expressing human Ptch1 confirmed that methiothepin specifically interacts with Ptch1 with a Kd of about 7 mM.…”
Section: Methiothepinmentioning
confidence: 90%
“…[81]) to bacterial proteins of the RND family (e.g., [82]). Concerning Ptch1, computational investigations were focused on cholesterol transport [77], recognition and binding [83], and mechanism of drug efflux and of inhibition [30,57,60]. Extensive molecular dynamics simulations of cholesterol molecules interacting with the transporter complemented available structural data by demonstrating cholesterol transport [77].…”
Section: In Silico Studies Of Ptch1mentioning
confidence: 99%
“…CDKN2A, TP53, and NRAS mutations were also detected in SCC [90,91], explaining the effectiveness of novel MM-employed therapeutic approaches also in SCC. Regarding BCC, the PTCH1, GLI1, SMO, and E2F5 mutations were detected, with specific inhibitors and antagonists being already available in clinical practice, while other molecules are still under investigation within clinical trials [92]. It is clear, however, that there are still many unknown gene mutations involved in skin cancers, as their potential influence on the dielectric properties of skin cells remains to be demonstrated.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Chronic antipsychotic use, genetic factors, and pathophysiological changes have been posited to explain the potentially reduced risk of cancer development in schizophrenia patients. For example, there is a growing body of evidence that antipsychotics may protect against the development of cancer; antipsychotics are now being repurposed as potential cancer therapies, with anticancer mechanisms of action in peripheral tissues still poorly understood [ 6 , 28 , 29 , 30 , 31 ]. Epidemiological studies have found that unaffected family members of patients with schizophrenia have reduced rates of cancer [ 4 , 32 ], suggesting that genetic factors contributing to schizophrenia risk may also reduce the risk of developing cancer.…”
Section: Cancer Incidence In Schizophreniamentioning
confidence: 99%